Contribution of spontaneously-fermented sourdoughs with pear and navel orange for the bread-making. (March 2018) - Yu, Yafang; Wang, Li; Qian, Haifeng; Zhang, Hui; Qi, Xiguang
Abstract: This study investigated the effects of spontaneous sourdoughs started with pear and orange fermentations on the quality attributes of white pan breads, focusing on acidification capacity, fermentation properties, free amino acids (FAA) concentration and bread properties. This work successfully developed that adding sourdough could improve the technological and nutritional properties of the bread, and that different substrates for sourdough led to differences in the bread characteristics. Breads made from sourdough exhibited lower pH (4.66–4.87) and greater acidity (3.95–4.46 mL) than the control breads. It was possible to decrease the gas production by adding sourdough, however, the gas retention ability enhanced evidently. The retention coefficients for pear and navel orange sourdoughs were 87.2% and 90.4%, respectively. Sourdough fermentation supported an appropriate acidic environment for improving the metabolic activity of some endogenous enzymes, resulting in increased specific volume and concentrations of FAAs. The 15 yeasts and 26 LAB isolates from the pear sourdough, the 21 yeasts and 18 LAB isolates from the navel orange sourdough were identified using 16S rRNA gene and 26S rRNA gene sequencing. All LAB isolates were identified as 3 species: Lactobacillus brevis, Lactobacillus plantarum, and Lactobacillus rossiae and all the yeasts as Saccharomyces cerevisiae . Highlights: Pears and navel oranges were used as substrates for spontaneous sourdoughs. Dough retention capacity was strengthened by spontaneous sourdoughs. Texture and FAAs concentration of breads were influenced by sourdoughs. The 15 yeasts and 26 LAB strains from the pear sourdough were identified. The 21 yeasts and 18 LAB strains from the navel orange sourdough were identified.